Optimalisasi Legalitas dan Pemasaran dalam Mendukung Pertumbuhan UMKM (Studi Kasus Pada UMKM di Kecamatan Sawahan Surabaya) - Maura Nathasya Audina Hidayat; Rida Perwita Sari (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to analyze efforts to optimize legality and marketing in supporting the growth of MSMEs (Micro, Small, and Medium Enterprises) in Sawahan District, Surabaya. MSMEs with complete legality can more easily participate in these events, potentially boosting their visibility and product sales. The data for this research was obtained through in-depth interviews and direct observations, providing a comprehensive view of the challenges and opportunities faced by MSMEs in Sawahan District. Data analysis shows that while obtaining an NIB is relatively easy with assistance from related agencies, acquiring a halal certificate remains a significant challenge due to complex procedures.